Princely Halych: Intriguing Prospects for Archaeological Research - Koval, Ihor (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
According to statistical data, permanent and local archaeological researches have covered only about ten per cent of the territory of Princely Halych, which opens up endless possibilities for research at the site of the ancient city. The chapter highlights the importance of the scientific and popular works by Antin Petrushevych, Lev Lavretskyi and Izydor Sharanevych, who in 1882 initiated the archaeological research on the mighty Principality of Halych (Galicia) and its capital, and the excavation of the first Christian church in Halych – the Church of the Holy Saviour mentioned in the Kyivan Chronicle. The little-known works of these scientists, which were published in Lviv newspapers in the 1880s, clearly show that Lavretskyi and Sharanevych’s findings received international acclaim and were a significant factor in rousing national consciousness and stimulating social activity of the Galician Ukrainians. It is difficult to explain the lack of interest in carrying out excavations outside the perimeter of the foundations of the Church, which could have enhanced the social, historical, topographical analysis of the monument and its surroundings. A particular fact that proves the importance of such research is the discovery of pendant seals, which modern sphragistics attributes to Prince Volodymyrko Volodarevych (1141- 1153). This conclusion is in good agreement with the Kyivan Chronicle and the findings of the archaeologists who excavated the Church of the Holy Saviour. All these facts provide grounds for the hypothesis concerning the location of the State Chancellery and the mysterious Palace of the 12th century Lords of Galicia.